Aerodynamic characterization and mission performance analysis of a light seaplane design - Gires, Ezanee; Mohamed Magdi, Ahmed Marwan; Abdul Hamid, Mohd Faisal; Md Zhahir, Md Amzari; Md Ali, Syaril Azrad; Mohd Rafie, Azmin Shakrine (Aerospace Society Malaysia, 2024)
This paper presents the modeling, aerodynamic characterization, and mission performance analysis of a seaplane based on the AeroVolga Borey, utilizing a baseline Rotax 912 ULS engine configuration. The seaplane, with its amphibious capabilities, plays a critical role in connecting remote regions, yet detailed aerodynamic analyses of such aircraft are scarce. The study aims to address these gaps by focusing on the seaplane's aerodynamic properties and mission performance. A 3D-printed model of the Borey seaplane was tested in an open-loop wind tunnel, providing lift and drag coefficients under various flight conditions. The highest lift to drag ratio was found to be 8.9. The aerodynamic data were integrated into a mission performance simulation to assess fuel burn, range, and performance in different flight phases The study finds that the aerodynamic and mission performance characteristics align closely with benchmark design data, highlighting the Borey's potential as a short-to-medium-range seaplane. The maximum range calculated is 685 km with error 7.4% relative to the design specification. The implications for future seaplane designs and the advancement of aviation technology are significant, particularly in enhancing fuel efficiency and operational range